EFEKTIVITAS CORE STRENGTHENING EXERCISE TERHADAP PRIMARY DYSMENORRHEA PADA REMAJA - Hanun Rifda Aziza; Marti Rustanti; Herdianty Kusuma (Jurusan Fisioterapi Poltekkes Kemenkes Surakarta, 2024)
Background : Teenager are very at risk for health problems, one of which is menstrual pain called dysmenorrhea. The occurrence of dysmenorrhea greatly affects daily activities. Dysmenorrhea, if not handled properly it can have an impact on reducing daily activities and quality of life. Objective : To determine the effectiveness of core strengthening exercise against primary dysmenorrhea in teenagers. Methods: This study used one group pre and post test with control design involving 114 subjects who were divided into two groups, namely the treatment group of 59 people and the control group of 55 people. Measurement of the degree of pain of dysmenorrhea is carried out during early and late treatment. The measuring instruments in this study are NRS and WaLLID Score . Result : Based on statistical testing after conducting a core strengthening exercise for 1 month, significant results were obtained with a p-value = 0.000 (p<0,05) which means that there is an influence of core strengthening exercise on the initial and final NRS values. In addition, when compared between the final NRS scores in both groups, better results were obtained in the treatment group than in the control group. Conclusion : The provision of core strengthening exercises affects reducing the degree of dysmenorrhea pain in teenagers.